Inhibition of Pitting Corrosion of the Stainless Steel by Dipyridinium Salts - Obaid, A.Y.; Al-Thabaiti, S.A.; Qusti, A.H.; Hermas, A.A. (Asian Journal of Chemistry, 2013)
The inhibitive actions of three sensitized derivatives of N,N'-diquaternized 4,4'-dipyridinium salts (TMdPyBr2, HMdPyBr2 and MPhdPyCl2) on general and pitting corrosion of the stainless steel (SS) in aerated 0.1 M HCl have been studied at different temperatures. Corrosion potential and polarization measurements proved that the three compounds act as mixed type inhibitors with dominant anodic and their adsorption on the steel surface obey Langmuir adsorption isotherm. The diquaternized salts inhibited the corrosion and improved the passivation of the stainless steel, their inhibition efficiencies (except for TMdPyBr2) increased with temperature. Electrochemical impedance measurements and optical microscopic investigation confirmed the inhibitive actions of these compounds and proved that both TMdPyBr2 and HMdPyBr2 inhibit the pitting initiation while MPhdPyCl2 is less efficient inhibitor against the pitting. The mechanism of corrosion inhibition was discussed in the light of the molecular structure of the dipyridinium salts.